2011
DOI: 10.1530/rep-11-0163
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine response induced by Chlamydia trachomatis in prostate derived CD45+ and CD45− cells

Abstract: The role of innate cells and their receptors within the male genital tract remains poorly understood. Much less is known about the relative contribution of different genital tract cells such as epithelial/stromal cells and resident leucocytes. In this study, we examined innate immune responses to Chlamydia trachomatis by prostate epithelial/stromal cells and prostate resident leucocytes. Murine prostate primary cultures were performed and leucocyte and epithelial/stromal cells were sorted based on surface prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…To our knowledge, all previous studies have only explored the effect of Ct on epithelial cells of the female reproductive tract 2022 , however as we have demonstrated here, Ct can also infect and affect the function of ESC. In light of this novel finding, we propose that ascending genital Ct infection might be a more complicated process than previously thought, as Ct could breach the epithelial barrier of the endometrium and infect other cell types such as stromal cells, endothelial cells or glandular epithelial cells (endometrial structure reviewed in ref.…”
Section: Discussionmentioning
confidence: 66%
“…To our knowledge, all previous studies have only explored the effect of Ct on epithelial cells of the female reproductive tract 2022 , however as we have demonstrated here, Ct can also infect and affect the function of ESC. In light of this novel finding, we propose that ascending genital Ct infection might be a more complicated process than previously thought, as Ct could breach the epithelial barrier of the endometrium and infect other cell types such as stromal cells, endothelial cells or glandular epithelial cells (endometrial structure reviewed in ref.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, based on the current study results, it may be concluded that both CXCL1 and CXCL9 are critical chemokines involved in the innate immune responses against C. trachomatis infection. Previous studies demonstrated that CXCL1 is produced by several immune and non-immune tissue/cell systems, including macrophages, neutrophils and epithelial cells with predominant neutrophil chemoattraction activities ( 19 ). Moreover, it has also been documented that CXCL9 play important roles in infiltrating of the activated T lymphocytes towards the infected and inflamed tissues ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mackern Oberti et al have examined the prostate epithelial/stromal cells dependent immune responses to C. trachomatis and observed that it could infect murine prostate cells by the development of large inclusions. Moreover, their results demonstrated that prostate cells have responded to C. trachomatis infection by production of pro-inflammatory chemokines inducing CCL2, CXCL1, and CXCL2 ( 19 ). They also observed that the chemokine productions by prostate cells were performed via activation with toll-like receptor, pathogen-associated molecular patterns interaction ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…C . trachomatis has been implicated as a microbial driver in prostate carcinogenesis and has also been shown to elicit chemokine production from immune cells and non-immune cells isolated from the prostate ( Oberti et al, 2011 ). Our prediction suggests a more specific role for ACBD6 in prostate cancer as a potential suppressor of NF κ B activity and downstream inflammation, as it was highly co-expressed with the two NF κ B inhibitors, NF κ B IA and NF κ BIE ( Pringle et al, 2012 ; Wu et al, 2006 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Performing this task in ARepA allowed us to recover several genes already associated with NF κ B and prostate cancer ( Davis, Kucuk & Sarkar, 1999 ; Perkins, 2012 ), in addition to original findings including MEN1 as a novel putative upstream regulator ( Bouwmeester et al, 2004 ; Hacker & Karin, 2006 ; Heppner et al, 2001 ; Wen et al, 2000 ) and ACBD6 as a potential downstream suppressor of NF κ B-activation ( Oberti et al, 2011 ; Pringle et al, 2012 ; Soupene et al, 2012 ; Wu et al, 2006 ). MEN1 was linked to cancer, prostate cancer and NF κ B by two main data sources.…”
Section: Discussionmentioning
confidence: 99%